2015
DOI: 10.1002/hep.27339
|View full text |Cite
|
Sign up to set email alerts
|

Astrocyte elevated gene‐1 and c‐Myc cooperate to promote hepatocarcinogenesis in mice

Abstract: Astrocyte elevated gene-1 (AEG-1) and c-Myc are overexpressed in human hepatocellular carcinoma (HCC) functioning as oncogenes. AEG-1 is transcriptionally regulated by c-Myc and AEG-1 itself induces c-Myc by activating Wnt/β-catenin signaling pathway. We now document cooperation of AEG-1 and c-Myc in promoting hepatocarcinogenesis by analyzing hepatocyte-specific transgenic mice expressing either AEG-1 (Alb/AEG-1), c-Myc (Alb/c-Myc) or both (Alb/AEG-1/c-Myc). WT and Alb/AEG-1 mice did not develop spontaneous H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
46
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(48 citation statements)
references
References 45 publications
(65 reference statements)
2
46
0
Order By: Relevance
“…Previous studies as well as our study manipulating AEG-1 expression in HCC cells showed that overexpression of AEG-1 promotes proliferation and increases anchorageindependent growth in soft agar (16,46); knockdown of AEG-1 was found to suppress proliferation and inhibit colony formation as well as induce apoptosis through suppression of IL-6 secretion (47,48). Further studies also demonstrated that enhanced AEG-1 expression in HCC cells generated large and highly vascular subcutaneous tumors compared to the control; correspondingly, downregulation of the expression of AEG-1 decreased the tumor formation rate and the growth of subcutaneous tumors in nude mice and the tumor volumes were found to be smaller than the control (16,47).…”
Section: Aeg-1 Accelerates the Growth Of Hccmentioning
confidence: 67%
See 1 more Smart Citation
“…Previous studies as well as our study manipulating AEG-1 expression in HCC cells showed that overexpression of AEG-1 promotes proliferation and increases anchorageindependent growth in soft agar (16,46); knockdown of AEG-1 was found to suppress proliferation and inhibit colony formation as well as induce apoptosis through suppression of IL-6 secretion (47,48). Further studies also demonstrated that enhanced AEG-1 expression in HCC cells generated large and highly vascular subcutaneous tumors compared to the control; correspondingly, downregulation of the expression of AEG-1 decreased the tumor formation rate and the growth of subcutaneous tumors in nude mice and the tumor volumes were found to be smaller than the control (16,47).…”
Section: Aeg-1 Accelerates the Growth Of Hccmentioning
confidence: 67%
“…As mentioned above, AEG-1 is regulated by Ha-ras through the PI3K/Akt/GSK3β/c-Myc pathway (62) in HCC. AEG-1 is transcriptionally regulated by c-Myc, and cooperates with c-Myc maternally imprinted non-coding RNAs, such as Rian, Meg-3 and Migr, which are implicated in the promotion of hepatocarcinogenesis (46). AEG-1-dependent anoikis resistance is also activated via the PI3K/Akt pathway and Bcl-2, and the PI3K inhibitor LY294002 was found to reverse the AEG-1-dependent effects on Akt phosphorylation, expression and anoikis resistance (54).…”
Section: Nf-κb and Phosphatidylinositol 3-kinase (Pi3k)/aktmentioning
confidence: 99%
“…Overexpression of AEG-1 in the poorly aggressive HCC cell line HepG3, which expresses a low level of AEG-1, significantly increases in vitro proliferation, invasion, anchorage-independent growth and chemoresistance, and in vivo tumorigenesis, angiogenesis, and metastasis in nude mice (7, 9 -11). These observations were further corroborated in a transgenic mouse with hepatocyte-specific overexpression of AEG-1 (Alb/AEG-1) that develops highly aggressive metastatic HCC in a diethylnitrosamine-induced HCC model (12,13). Conversely, knockdown of AEG-1 in highly aggressive QGY-7703 cells, expressing high levels of AEG-1, significantly abrogates in vivo tumorigenesis (7,10).…”
mentioning
confidence: 66%
“…Alb/AEG-1 and AEG-1KO Mice-Generation and characterization of a hepatocyte-specific AEG-1 transgenic mouse (Alb/ AEG-1) and an AEG-1 knock-out (AEG-1KO) mouse have been described previously (12)(13)(14) Patient Samples-Serum samples were collected from hepatitis C virus-HCC patients (n ϭ 23) and 14 healthy volunteers. These studies are approved by the Institutional Review Board of the University of Virginia.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, Li et al demonstrated that AEG-1 promotes gastric cancer progression through a positive-feedback Toll-like receptor 4/NF-B signaling-related mechanism (14). Moreover, Robertson and colleagues found that AEG-1-deficient mice display resistance to N-nitrosodiethylamine-induced hepatocellular carcinoma and lung metastasis (18).…”
mentioning
confidence: 99%